Here is a (false) proof that 3 = 4. If 3 were really equal to 4, the entire mathematical foundation would crumble and centuries of math would be obliterated.
Let x = 1 and y = 1. It is clear that
x = y. Multiplying x to both sides, we get
x^2 = xy. Subtracting y^2 to both sides, we have
x^2 - y^2 = xy - y^2. Factoring both sides,
(x - y)(x + y) = y(x - y). Dividing both sides by (x - y), we have
x + y = y. Adding 2 to both sides,
x + y + 2 = y + 2. Substituting in back x = 1 and y = 1
1 + 1 + 2 = 1 + 2
4 = 3
2007-02-09 04:02:08
·
answer #1
·
answered by Puggy 7
·
2⤊
1⤋
well its not just 3 & 4, you can prove any 2 numbers to be equal by violating some laws. replace the numbers you want to be equal by examining the following.
say you want to prove 3 = 4
(3 + 4 )x(3 - 4) = 7 x (3 - 4)
3x3 + 4x3 - 3x4 - 4x4 = 7x3 - 7x4
3x3 + 3x4 - 7x3 = 4x3 + 4x4 - 4x7
3 ( 3 + 4 -7 ) = 4 ( 3 + 4 -7 )
cut off ( 3 + 4 - 7 ) on both sides
so now
3 = 4
you can actually do this with any two numbers :)
try substitutin 3,4 & 7 with respective numbers for an example .
say U want to prove 2 = 6
then replace 3 with 2
4 with 6
and 7 with 8
hope you understand :)
Enjoy
P.S = the trick is you cant cut the phrase ( 3 + 4 - 7 ) as it is 0 (zero) lol!!!
2007-02-09 04:27:57
·
answer #2
·
answered by CodeRed 3
·
0⤊
0⤋
3=4 is almost impossible. Unless you take 3 people, 2 males and 1 female. Have them engage in intercourse and produce 1. Thus you would have 3=4. Or aside from reproduction use an algebraic equation, where you solve for an unknown. 3?=4 Now you must solve for the unknown.
2007-02-09 04:15:57
·
answer #3
·
answered by Proud Momma of 4mth old Boy 3
·
0⤊
0⤋
yes i'll show you.
0^3=0^4
=>since bases are equal ,even the exponents should be equal.
since base 0=0. .there fore3=4.
thus actually talking is not right ,but a simple trick to solve this problem.got it!
2007-02-09 04:04:20
·
answer #4
·
answered by achyut s 1
·
0⤊
0⤋
12/3 =4
12 divided by 3= 4
2007-02-09 03:56:19
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
It is possible if you use algebra.
You can show this by using this expression.
3x = 4y
Where x and y are unknown factors.
So, x = 4y/3 , and y = 3x/4
If x = 1, then you get
3 = 4y
So, y = 3/4
If y = 1, then you get
3x = 4
So, x= 4/3 or 1.1/3 (one and one-third).
2007-02-09 03:59:07
·
answer #6
·
answered by Think Richly™ 5
·
0⤊
1⤋
I think it is important to stress that "trick" in the proof is dividing by (x-y) which is equal to 0.
2007-02-09 04:03:38
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
By violating the laws of nature and/or mathematics.
2007-02-09 03:55:34
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋
Highly convoluted algebra could'nt solve that one for you, sorry!!
2007-02-09 03:56:07
·
answer #9
·
answered by RobLough 3
·
1⤊
0⤋
by changing the mathematics rules :|
2007-02-09 04:40:44
·
answer #10
·
answered by GoRgEoUs Me 1
·
0⤊
0⤋